Porcupine bezoar: in vitro antioxidant and anti-proliferative effects - Abdullah Asuhaimi, Faizah; Yuhanis, Alaina; Kamal, Tara; Opeyemi Roheem, Fatimah; Ahmed, Qamar Uddin; Hamdan, Salehhudin; Khatib, Alfi; Mohammad, Mardhiah; Johan, Muhammad Farid; Hashim, Ridzwan; Abdul Wahab, Ridhwan (1, 2017)
Objectives: Porcupine bezoar (PB) is a mass of undigested organic and inorganic materials formed within the gastrointestinal tract of the porcupine. PB has been claimed to possess medicinal properties to treat different types of diseases including cancer. However, these traditional claims are yet to be scientifically ascertained and properly validated. Hence, this study was aimed to evaluate antioxidant and anticancer activities of PB through different biological assays.